Pengaruh Remunerasi, Lingkungan Kerja, dan Work-Life Balance terhadap Kinerja Karyawan Studi pada Karyawan PT Duta Utama Mustika di Tangerang - Muhammad Harun Al-Rossyid; Deden Kurniawan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of remuneration, work environment, and work-life balance on employee performance at PT Duta Utama Mustika. The background of this research lies in the importance of improving employee performance to achieve optimal company goals. Factors such as a fair remuneration system, a comfortable work environment, and maintaining a balance between work and personal life are believed to significantly impact employee productivity and performance. This research employed a quantitative approach with a sample of 80 employees selected using a specific sampling technique. Data were collected through questionnaires using a five-point Likert scale to measure variables including remuneration, work environment, work-life balance, and employee performance. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results of the study indicate that remuneration has a significant effect on employee performance, meaning that providing appropriate and fair compensation can enhance motivation and work performance. Similarly, the work environment significantly influences performance, suggesting that a safe, comfortable, and supportive workplace contributes to employee productivity. In addition, work-life balance was also found to have a significant effect on performance, demonstrating that balancing job demands with personal life is essential for employees to remain focused and perform effectively. Based on these findings, the company is recommended to improve its remuneration system, create a more conducive work environment, and implement policies that promote work-life balance in order to enhance overall employee performance sustainably.